Unraveling the association and regulatory role of miR-146b-5p in coronary artery disease - Xiaozhu Ma; Shuai Mei; Yi He; Qidamugai Wuyun; Li Zhou; Ziyang Cai; Qiushi Luo; Yi Wen; Jiangtao Yan (BMC Cardiovascular Disorders)
Abstract Background Coronary artery disease (CAD), one of the most prevalent cardiovascular diseases, is a critical health issue that affects millions of individuals worldwide. It has been reported that miR-146b-5p exhibited a strong correlation with inflammatory responses and atherosclerosis. However, its association with the incidence and severity of CAD has not been substantiated in a large cohort. In the study, we focus on the expression of miR-146b-5p in peripheral blood mononuclear cells (PBMCs) of patients with CAD and preliminarily investigate its function and underlying mechanism. Methods and results The study encompassed a total of 452 participants, consisting 295 patients with CAD and 157 individuals without CAD. Quantitative reverse transcription–polymerase chain reaction (qRT–PCR) was performed to assess miR-146b-5p expression in PBMCs. We found that miR-146b-5p was significantly increased in PBMCs of patients with CAD compared with the control group. Binary logistic regression revealed that miR-146b-5p was associated with CAD. Receiver Operation Characteristic (ROC) analysis showed that the sensitivity and specificity of miR-146b-5p in discriminating CAD patients from non-CAD patients were meaningful. Subsequent subgroup analysis showed that miR-146b-5p was related to the severity of CAD. Furthermore, gain- and loss-of-function experiments in THP-1 cells showed that miR-146b-5p inhibited inflammation, cell proliferation, and migration. Mechanically, miR-146b-5p was involved in the classical NF-κB inflammatory pathway by directly targeting IKKβ. Conclusion Our study revealed that miR-146b-5p was higher in the PBMCs of CAD patients than non-CAD individuals, and established a correlation between miR-146b-5p and occurrence and severity of CAD. In addition, the inflammatory role of miR-146b-5p is mediated by targeting IKKβ.